Boiled potato waste silage as an alternate roughage for goats - RAINA, SAHIL; SHARMA, R K; RASTOGI, ANKUR; PATHAK, A K; KHAN, NAZAM; SHARMA, VIJAY KUMAR (The Indian Journal of Animal Sciences, 2023)
A feeding trial (60 days) was conducted to gauge the nutritional attributes of boiled potato (Solanum tuberosum) peel waste silage and to analyse its feeding effect on intake and utilization of nutrients in goats. Twelve local, non-descript, adult male goats were randomly divided into two groups. Each group was given ad lib. wheat straw, concentrate mixture @ 20 g/KgW0.75 and silage @ 75 g/KgW0.75 Based on variation in source of silage the groups were classified as maize silage (MS) or potato peel waste silage (PPS) groups. Despite the higher crude protein concentration PPS could be successfully ensiled with achievement of necessary pH fall, possibly due to effect of boiling on starch granules to render it readily fermentable and/or heat damaged CP. In both the groups live weight of the goats was maintained throughout the trial. The PPS formed about 20.2% of the total ration intake (on DM basis). Nutrient digestibility (%) was similar between dietary groups, except NFE and NDF digestibility, which was considerably higher in PPS group. It may be concluded that the ensiled boiled potato peel waste may be utilized as a constituent of adult goat ration without compromising nutrient intake, digestibility, plane of nutrition and nutrient balance.